Diversity, Uses and Management of Plant Resources in Leasehold Forests of Makwanpur District, Nepal - Kunwar, Ripu M; Adhikar, Nirmal (The Initiation, 2010)
DOI: 10.3126/init.v1i0.2688 The Initiation Vol.1 2007 p.88-92